Evaluation of sperm retrieval rate with bilateral testicular sperm extraction in infertile patients with azoospermia - Mohammad Reza Moein; Mahmoud Reza Moein; Jalal Ghasemzadeh; Soheila Pourmasoumi (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: About 10% to 15% of infertile men have azoospermia, which could be obstructive or non-obstructive. Diagnostic biopsy from the testis and recently testicular sperm extraction (TESE) are the most precise investigations in these patients. Testicular biopsy can be done unilaterally or bilaterally. The worth of unilateral or bilateral testicular biopsy in men with azoospermia is controversial. Objective: To evaluate the necessity of bilateral diagnostic biopsy from the testis in new era of diagnosis and treatment of male infertility. Materials and Methods: In this retrospective study, we reviewed the results of testis biopsy in 419 azoospermic men, referred to Yazd Research and Clinical Center for Infertility from 2009-2013. Patients with known obstructive azoospermia were excluded from the study. Results: In totally, 254 infertile men (60.6%) were underwent unilateral TESE, which in 175 patients (88.4%) sperm were extracted from their testes successfully. Bilateral testis biopsy was done in 165 patients (39.4%) which in 37 patients (22.4%), sperm were found in their testes tissues. Conclusion: Due to the low probability of positive bilateral TESE results especially when we can't found sperm in the first side, we recommend that physicians re-evaluate the risk and benefit of this procedure in era of newer and more precise technique of sperm retrieval like micro TESE